VARIOUS LANGUAGE OF ASONGAN TRADERS AT THE BEACH OF BOCOR KEBUMEN - Anis Setiyanti (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2018)
This study was conducted to assess various languages trader deals in Bocor Beach Kebumen in terms of perspektik sociolinguistics. The aim of research to find out the deals utterances used by hawkers at Bocor Beach Kebumen, knowing offers a variety of language used by hawkers at Bocor Beach Kebumen, and knowing use of vocabulary that deals used by hawkers at Bocor Beach Kebumen. This study used a qualitative approach. The method used in this research is descriptive and analytical. The data used in this research is data in the form of a variety of language associated with language diversity offers Bocor beach hawkers. The results of the study deals buying and selling a variety of language, which is rarely done because of language preservation demands an understanding of the other person. Keywords: language diversity, merchant, sociolinguistic